(3VeGfGJ MQjI Jchjf GdCMRGH GdSjGSjI aj GdfXGe GdbGfhfj GdeUQj (B:s (3OQGSI JMdjdjI (B/ s - (3HGgQ eMeO YHO GdQMefs; (3KQhJ YHO GdYGd CMeOs; (3TYHGf CMeO QeVGfs; (3LGeYI CSjhWs (3cdjI GdMbhbs ((3CSjhW(B:s (3cdjI GdMbhb(B- (3LGeYI CSjhW,s, 2018)
(3JgOa GdVeGfGJ GdbGfhfjI Gdi EbGeI fXGe Mce OjebQGWi , JUGf ajg cGaI GdMbhb hGdMQjGJ GdYGeI hGdJi Ydi QCSgG MQjI Jchjf GdCMRGH GdSjGSjI hVeGfGJgG ,hJchf GdSdWI COGI dJMbjb GdQaGgjI hGdSYGOI dcd CaQGO GdeLJeY Ohf JejR Ch JaQbI dGi SHH ef GdCSHGH , HeYfi jLH ENVGY cGaI GdSdWGJ hcGaI GdeDSSGJ GdbGfhfjI HMSH JOQLgG cGdbhGYO GdOJhQjI hGdbhGfjf GdYGOjI hGddhGFM hGdbQGQGJ(B.s
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI CSjhW, cdjI GdMbhb, bSe GdbGfhf GdOSJhQj (B2018s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 459-483 (3UaMIs
Keywords: (3GdbGfhf GdOSJhQjs; (3GdCMRGH GdSjGSjIs; (3GdVeGfGJ GdOSJhQjIs; (3GdefGaSI GdMRHjIs; (3GdJYOOjI GdUhQjI ddCMRGHs; (3GdeHGOF GdYGeI dOSJhQ (B1971s; (3GdEYdGfGJ GdOSJhQjIs; (3GdfXGe GdOjebQGWjs; (3SjGOI GdbGfhfs; (3QSGFd LGeYjIs -- (3LGeYI CSjhWs